2018
DOI: 10.1080/01635581.2018.1424346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-Arginine Supplementation on Leukogram, Inflammatory Bowel Infiltrates and Immunoglobulins with 5-FU Use in Rats

Abstract: This study evaluated the effects of L-arginine supplementation on blood parameters, kidney and liver function, immunoglobulins and noninflammatory infiltrates in the small intestines of rats subjected to chemotherapy with 5-fluorouracil (5-FU). Thirty-two Wistar rats were randomly distributed into 4 groups (8 rats/group): an untreated control group, and test groups receiving one dose of 5-FU (G group), one dose of 5-FU and 295 mg L-arginine/day (G group) or one dose of 5-FU and 458 mg L-arginine/day (G group).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…l-Arginine has multiple beneficial effects on the intestines [19,26], although we found that its protective effect was only exerted in a specific concentration range. As shown in Fig.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…l-Arginine has multiple beneficial effects on the intestines [19,26], although we found that its protective effect was only exerted in a specific concentration range. As shown in Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Dysfunction of TJs has been reported to be associated with increased permeability of the intestinal epithelium [17] and the development and progression of intestinal disorders [18]. HS decreases the expression of TJs and leads to intestinal barrier dysfunction [19]. Zhang et al also reported that heat stress disrupts the expression of TJ proteins in chickens, such as mucin-2, claudin-1, and occludin [20].…”
Section: The Gastrointestinal Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Arginine, in combination with other substances in the body, enhances the immune system and regulates IL-2 gene expression through methylation [ 42 ]. Moreover, l -arginine supplementation can alleviate the side effects of thrombocytopenia and leukopenia and enhance IL-2 immunotherapy [ [43] , [44] , [45] , [46] ]. Thus, QJSB may enhance the immune system and hematopoietic function through the components of Equus asinus L. by regulating the metabolic pathway of arginine.…”
Section: Discussionmentioning
confidence: 99%
“…Many research studies have proved that arginine could improve gastrointestinal function and gastric ulcer healing, accelerate intestinal mucosal regeneration, enhance bacterial clearance, and reduce histological bowel necrosis (Wang et al, 2009). Meanwhile, a new report observed that arginine could attenuate 5-fluorouracil-induced thrombocytopenia and neutropenia (Balmant et al, 2018). Moreover, a large number of experiments have also proved that supplemental arginine administration was beneficial in reducing myelosuppression and gastrointestinal toxicity caused by chemotherapy (Morris, 2006;Morris et al, 2017;Xia et al, 2016).…”
Section: Discussionmentioning
confidence: 99%